A study on the micromixing performance in microreactors for polymer solutions. Issue 9 (7th May 2018) - Zha, Li; Pu, Xin; Shang, Minjing; Li, Guangxiao; Xu, Wenhua; Lu, Qinghua; Su, Yuanhai
Abstract : Microreactors are widely applied for various polymerization processes to produce polymers with controlled molecular weight and structures. In this work, the mixing of polymer solutions in capillary microreactors was investigated with the aid of the biazo‐coupling reaction system and high‐speed camera. A smaller inner diameter, a higher Dean number and a lower Torsion number could promote the micromixing performance in microreactors. Unlike the mixing of Newtonian fluids in microreactors or micromixers, the mixing of polymer solutions follows different mechanisms and it is more difficult to reach homogeneous condition. However, the good micromixing performance in capillary microreactor systems for polymer solutions still could be obtained with high shear rates and long enough capillary length at relatively high correlated Reynolds numbers (NRe > 29). Furthermore, the micromixing time in the capillary microreactors was evaluated based on a modified stretching efficiency model and its value was in the range of 0.1–8.0 ms. © 2018 American Institute of Chemical Engineers AIChE J, 64: 3479–3490, 2018